Creating a mule deer habitat mitigation tool for energy extraction activities - Boone, Randall B., speaker (Colorado State University. Libraries, 2013)
In the last nine months, Randy has worked with a team of resource managers and scientists led by Ted Toombs of the Environmental Defense Fund to design an approach to quantify changes to mule deer habitat. The overall goal is to support a habitat exchange. Those who disturb habitat, such as those in the energy extraction industry, may trade habitat disturbance credits with others who are in a position to improve habitat for mule deer. Both the magnitude and type of disturbance to mule deer habitat must be considered, and the cost of assessment of habitat should be commensurate with the value of the original project. The group designed site measurements that depend upon local field-based measures of mule deer habitat and context measures of suitability that may be accessed through spatial analyses. Randy will review the components of the site and context measures. Each is documented, with a user's manual and field guide. Field testing and calibration of the method was conducted in July 2013, and refinement of the methods by the science team will occur soon.
Presented at the Fall 2013 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Community, Energy Development and the Environment", November 19, 2013, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Dr. Randy Boone has been with the Natural Resource Ecology Laboratory for more than a decade, and is a founding faculty member of the Department of Ecosystem Science and Sustainability. He is also a faculty member of the Graduate Degree Program in Ecology. Randy is a wildlife ecologist with training from Oregon State University and the University of Maine. He received his PH.D. in Wildlife Ecology from the University of Maine in 1996. After completing graduate work at the University of Maine, he joined Colorado State University. His experience is diverse, with research in spatial analyses and GIS, ecosystem modeling, landscape ecology, database management, biogeographical relationships of birds and plants, species/habitat relationships, wildlife and pastoral livestock mobility, spectroscopy, cluster analysis, and telemetry techniques.
Recorded speech and PowerPoint presentation.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: conservation; quantification approach; population analysis; anthropogenic disturbances; Colorado; Mule Deer Habitat Exchange; oil and gas; wells